Use of trastuzumab in the treatment of solid tumors - Charliński, Grzegorz; Boguradzki, Piotr (Contemporary Oncology/Współczesna Onkologia, 2003)
The use of monoclonal antibodies is one of the new approaches of cancer treatment. The primary condition for their use is the identification of the target molecule on cancer cells that can induce immunity and in consequence allow for antibody production. Furthermore, this molecule has to be expressed on cancer cells with some selectivity. The first antibody utilized in the trea- tment of solid tumors is trastuzumab, which is a humanized monoclonal antibody antyHER2 i.e. antibody against the receptor belonging to a family of the epidermal growth factor receptors. This receptor is quite frequently overex- pressed on tumors of epithelial origin. While binding to the HER2 receptor’s extracellular domain trastuzumab inhibits signal transduction to the nucleus. Moreover, it accelerates HER2 receptor internalization and deterioration and it stimulates antibody dependent complement cytotoxicity. Recently, clinical studies have shown that HER2 receptor’s overexpression correlates with poor prognosis in breast cancer patients. In comparative studies, combined treatment-chemotherapy with trastuzumab was found to induce statistically significantly longer survival in breast cancer patients compared with chemotherapy alone. Studies evaluating both HER2 receptor overexpression and the possibility of using trastuzumab in other endothelial tumors such as: non small cell lung cancer, ovarian cancer, bladder cancer, gastrointestinal tract tumors, pancreatic tumor and other are in progress. This article reviews the current status of the knowledge on this subject.